Inconsistent effects of local and landscape factors on two key pests in Israeli vineyards. (18th June 2021) - Krasnov, Helena; Cohen, Yafit; Goldshtein, Eitan; Ovadia, Shmuel; Sharon, Rakefet; Harari, Ally R.; Blank, Lior
Abstract: An ecoinformatics approach was used to test how two noxious species in grapevines with varying host preferences and movement characteristics: the European grapevine moth ( Lobesia botrana ), and a parasitic fungus, the grape powdery mildew ( Uncinula necator ), are affected by local and landscape variables. Data were collected from 202 vineyards during four seasons: 2013, 2014, 2016 and 2017 and analysed using generalized mixed models. We hypothesized that the European grapevine moth would be affected most by the landscape variables, while the grape powdery mildew would be affected most by local ones. We found that the number of sprayings during the season was an important variable explaining variation in infestation levels between vineyards for both species. At the landscape scale, we found larger variations in the relationship between the studied variables and the two pests, but both were also affected by the surrounding land use including areas of deciduous orchards. Understanding the factors that affect the occurrence of various pests in the same environment might improve farmers' decision‐making.